1996
DOI: 10.1042/bj3140427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a triplex-binding ligand on triple helix formation at a site within a natural DNA fragment

Abstract: We have used DNase I footprinting to examine the effect of a triplex-binding ligand on the formation of parallel intermolecular DNA triple helices at a mixed sequence target site contained within a natural DNA fragment (tyrT). In the presence of 10 microM ligand (N-[2-(dimethylamino)ethyl]-2-(naphthyl)quinolin-4-ylamine), the binding of CTCTTTTTGCTT (12G) to the sequence GAGAAAAATGAA (generating a complex containing 8 x T x AT, 1 x G x TA and 3 x C+ x GC triplets) was enhanced 3-fold at pH 5.5. When the oligon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 27 publications
(38 reference statements)
1
20
2
Order By: Relevance
“…It can be seen that the oligonucleotide still produces a footprint at this site when the DNA is complexed to the nucleosome cores. Parallel triplex formation at this site therefore appears not to be hindered by wrapping the DNA fragment around the nucleosome cores, and contrasts with our previous results with tyrT (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) (37). We can exclude the possibility that this footprint (and others described below) is caused by interaction of the oligonucleotide with a small amount of contaminating free DNA since we have shown that in every instance at least 95% of the DNA is associated with the nucleosome cores, even after adding the triplex-forming oligonucleotide.…”
Section: Resultscontrasting
confidence: 99%
“…It can be seen that the oligonucleotide still produces a footprint at this site when the DNA is complexed to the nucleosome cores. Parallel triplex formation at this site therefore appears not to be hindered by wrapping the DNA fragment around the nucleosome cores, and contrasts with our previous results with tyrT (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) (37). We can exclude the possibility that this footprint (and others described below) is caused by interaction of the oligonucleotide with a small amount of contaminating free DNA since we have shown that in every instance at least 95% of the DNA is associated with the nucleosome cores, even after adding the triplex-forming oligonucleotide.…”
Section: Resultscontrasting
confidence: 99%
“…Although the nucleotides in the linker region of the TFO were designed according to standard antiparallel triplex rules, they were not expected to bind tightly to the underlying duplex because the TFO strand contained many pyrimidine bases, which interact only very weakly, if at all, with the purine-rich strand of the duplex. To assess whether triplex formation occurred in the linker region, we used DNase I footprinting since regions of a duplex that form triplexes are protected from DNase I cleavage ( , ). If nucleotides in the linker were participating in a triplex, the footprint would extend beyond the core footprint produced by a TFO with no additional nucleotides (Figure A, lane 3, TFO3AA).…”
Section: Resultsmentioning
confidence: 99%
“…In this paper we examine the formation of both parallel and antiparallel triplexes at target sites within two fragments derived from tyrT DNA, when reconstituted with nucleosome core particles. Previous studies have demonstrated the formation of parallel triplexes at this target site [26], while the rotational position of the native fragment has been well documented [13].…”
Section: Introductionmentioning
confidence: 85%
“…The native tyrT DNA fragment contains a run of purines between positions 43 and 54, interrupted by a single thymine at position 46. We changed this residue to adenine by site-directed mutagenesis using the PCR [26], generating tyrT(46A), whose sequence is shown in Figure 1(A). This produces a fragment containing 12 consecutive purine residues, which can be used as a target site for triplex formation using the oligonucleotides shown in Figure 1(B).…”
Section: Dna Fragmentsmentioning
confidence: 99%